PEMBUATAN BAHAN AJAR BERMUATAN KECERDASAN KOMPREHENSIF UNTUK MATERI PENGUKURAN, PENJUMLAHAN VEKTOR, DAN GERAK LURUS UNTUK KELAS X SMA SEMESTER I - Ramah Dhani; Asrizal Asrizal; Gusnedi Gusnedi (Universitas Negeri Padang, 2016)
Learning material which is used in Physics learning should support to achieve of core competencies in curriculum 2013 comprehensively. In fact learning material which is used in school doesn’t intregrated four core competencies comprehensively yet. A solution to solve this problemis to apply the learning material by including the comprehensive competencies. The purpose of this research is to investigate the description, validity, practicality, and effectiveness of learning material. The type of research is Research and Development (R&D). The research design to perform the limited test is bofore and after treatment. The object of this research is a learning material by including the comprehensive competencies. The instruments which are used in this research as follow test validation sheet, practicality test sheet, and effectiveness test sheet consisting of the test result of the study, spiritual attitude observation, emotional attitude observation, and students skill assessment. Product and data analysis techniques are analysis of product validity, analysis of practicality, and analysis of effectiveness. Based on the data analysis that has been done can be stated two research result. First, the product description is already appropriate design that consist of learning guidance, competencies, learning material, supporting information, exercises, worksheet, evaluation, and feedback; and the validity of the learning material are very valid with average value 84.85. Second, the value of the practicality of learning material are very practice with average value 83.54 and it is effective used in Physics learning